KAJIAN HERMENEUTIKA TERHADAP FENOMENA DAN TEKS AGAMA (AL-QUR’AN DAN HADIS NABI) - Dadang Darmawan (Holistic al-Hadis, 2016)
Prophet Muhammad Saw. as a messenger of Allah has indeed performed hermeneutical tasks. He conveyed, explained and interpreted messages from Allah to mankind. This paper itself will try to show that hermeneutical principles have been applied by the prophet Muhammad, long before the theory of hermeneutics formulated by western philosophers. Therefore, the efforts to understand the phenomenon and religious texts, especially hadith, with a hermeneutic approach is not a taboo.